2012
DOI: 10.1093/brain/aws238
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarker supported diagnosis of Creutzfeldt–Jakob disease and rapid dementias: a longitudinal multicentre study over 10 years

Abstract: To date, cerebrospinal fluid analysis, particularly protein 14-3-3 testing, presents an important approach in the identification of Creutzfeldt–Jakob disease cases. However, one special point of criticism of 14-3-3 testing is the specificity in the differential diagnosis of rapid dementia. The constant observation of increased cerebrospinal fluid referrals in the national surveillance centres over the last years raises the concern of declining specificity due to higher number of cerebrospinal fluid tests perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 42 publications
(61 reference statements)
6
104
1
5
Order By: Relevance
“…Measurement of 14‐3‐3s in CSF has been used clinically as a diagnostic biomarker for Creutzfeldt‐Jakob Disease (CJD), although recent studies have demonstrated that the specificity for CJD is lower than initially thought 48, 49, 50, 51. However, this body of research has demonstrated that 14‐3‐3 measurements in CSF are reliable and stable in patients, and can help with diagnosis in the right clinical context 48, 49. Further evaluation of 14‐3‐3 phosphorylation in CSF and plasma is indicated for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of 14‐3‐3s in CSF has been used clinically as a diagnostic biomarker for Creutzfeldt‐Jakob Disease (CJD), although recent studies have demonstrated that the specificity for CJD is lower than initially thought 48, 49, 50, 51. However, this body of research has demonstrated that 14‐3‐3 measurements in CSF are reliable and stable in patients, and can help with diagnosis in the right clinical context 48, 49. Further evaluation of 14‐3‐3 phosphorylation in CSF and plasma is indicated for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that deregulated tau may be reflecting the neuronal and axonal damage present in brain tissue and, as a consequence, the presence of increased tau levels is not a specific event for AD. Accordingly, transient tau increments have been also reported in acute stroke [123], and the most increased tau levels are observed in prion diseases such as in CJD, where massive neuronal cell death is present [124,125]. Higher CSF tau is also associated with smaller brain volume in individuals with AD [126].…”
Section: Taumentioning
confidence: 98%
“…El análisis de algunas proteínas, como la proteína 14-3-3, es útil y su elevación en LCR representa daño neuronal aunque no es específico de ECJ (15) y tiene una mayor sensibilidad en la esECJ que en las otras formas. Según Chohan et al la proteína 14-3-3 tiene una sensibilidad de 86% y una especificidad de 74% en fases avanzadas de la enfermedad (16) .…”
Section: Torres-ramírez L Et Alunclassified